Canalicular Network Morphology is the Major Determinant of the Spatial Distribution of Mass Density in Human Bone Tissue: Evidence by Means of Synchrotron Radiation Phase‐Contrast nano‐CT. (February 2015) - Hesse, Bernhard; Varga, Peter; Langer, Max; Pacureanu, Alexandra; Schrof, Susanne; Männicke, Nils; Suhonen, Heikki; Maurer, Peter; Cloetens, Peter; Peyrin, Francoise; Raum, Kay
ABSTRACT In bone remodeling, maturation of the newly formed osteonal tissue is associated with a rapid primary increase followed by a slower secondary increase of mineralization. This requires supply and precipitation of mineral into the bone matrix. Mineral delivery can occur only from the extracellular fluid via interfaces such as the Haversian system and the osteocyte pore network. We hypothesized that in mineralization, mineral exchange is achieved by the diffusion of mineral from the lacunar‐canalicular network (LCN) to the bone matrix, resulting in a gradual change in tissue mineralization with respect to the distance from the pore‐matrix interface. We expected to observe alterations in the mass density distribution with tissue age. We further hypothesized that mineral exchange occurs not only at the lacunar but also at the canalicular boundaries. The aim of this study was, therefore, to investigate the spatial distribution of mass density in the perilacunar and pericanalicular bone matrix and to explore how these densities are influenced by tissue aging. This is achieved by analyzing human jawbone specimens originating from four healthy donors and four treated with high‐dosage bisphosphonate using synchrotron radiation phase‐contrast nano‐CT with a 50‐nm voxel size. Our results provide the first experimental evidence that mass density in the direct vicinity of both lacunae (p < 0.001) and canaliculi (p < 0.001) is different from the mean matrix mass density, resulting in gradients with respect to the distance from both pore‐matrix interfaces, which diminish with increasing tissue age. Though limited by the sample size, these findings support our hypotheses. Moreover, the density gradients are more pronounced around the lacunae than around the canaliculi, which are explained by geometrical considerations in the LCN morphology. In addition, we speculate that mineral exchange occurs at all interfaces of the LCN, not only in mineralization but also in mineral homeostasis. © 2014 American Society for Bone and Mineral Research.